3y-9-(4-y)=2y-2

Simple and best practice solution for 3y-9-(4-y)=2y-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-9-(4-y)=2y-2 equation:


Simplifying
3y + -9 + -1(4 + -1y) = 2y + -2
3y + -9 + (4 * -1 + -1y * -1) = 2y + -2
3y + -9 + (-4 + 1y) = 2y + -2

Reorder the terms:
-9 + -4 + 3y + 1y = 2y + -2

Combine like terms: -9 + -4 = -13
-13 + 3y + 1y = 2y + -2

Combine like terms: 3y + 1y = 4y
-13 + 4y = 2y + -2

Reorder the terms:
-13 + 4y = -2 + 2y

Solving
-13 + 4y = -2 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
-13 + 4y + -2y = -2 + 2y + -2y

Combine like terms: 4y + -2y = 2y
-13 + 2y = -2 + 2y + -2y

Combine like terms: 2y + -2y = 0
-13 + 2y = -2 + 0
-13 + 2y = -2

Add '13' to each side of the equation.
-13 + 13 + 2y = -2 + 13

Combine like terms: -13 + 13 = 0
0 + 2y = -2 + 13
2y = -2 + 13

Combine like terms: -2 + 13 = 11
2y = 11

Divide each side by '2'.
y = 5.5

Simplifying
y = 5.5

See similar equations:

| 2y^2+7y-30=0 | | 5s^3+4s^2-10s-8=0 | | 0.2x+0.6=-1.2 | | 3(x+5)+2(4x-5)=32 | | 4(4x-2.4)=2x-9.6 | | 2x+37=23 | | 6.6-9h=7.5 | | x-2*x-9=-10 | | (2u+5)(9+u)=0 | | 4k-12=28 | | h=2+23t-16t^2 | | =9p | | 6-4r=3r-21 | | 180-x=3(90-x)+20 | | 5p+16p+24+6= | | 5x-11y=4 | | 6a^3=12a-5a-10 | | -6+2.4n=2.3-n | | 5x+2-2x+5= | | 8+5f=-12 | | x^2+9x+15=15 | | 7X+3X=8+X+20-1 | | 4x^2+66x-240=0 | | 1-p=-1 | | x=-25+5y | | 3x+1=15+5x | | 5x+.50y=190 | | q^2-10q-20=0 | | x^2+y^2+2x+10y-10=0 | | -(3xy-9)+3(4xy+6)= | | 33+Y=X | | 3(x-7)=23 |

Equations solver categories